CONFLICT ANALYSIS OF NOVEL MAIN CHARACTER: A DISCOURSE PERSPECTIVE - I Gusti Ayu Nila Wijayanti; I Nengah Laba (Denpasar Institute, 2020)
This study aims to analyze the conflicts of main characters depicted in the Sidney Sheldon novel entitled â€œTell Me Your Dreamsâ€ published in 1998 using both discourse analysis approach and textual analysis. It is to find out how discourse can be formally use to analyze and reveal the internal and external conflicts of the main characters using a medium of lexical choices and the flow of the dialog among the characters. This study used a qualitative descriptive research method. It is concerned with the description and explanation of phenomena involving the main characters of the novel. The lexical choices and some linguistic features used in the dialog among the main characters shows show both internal and external conflicts in this novel. In this novel there are also external conflicts. Using certain lexical terms in the plot, this novel is packed with neat stories and provides images and knowledge of life for readers.